Effect of Anticholinergic Medications on Falls, Fracture Risk, and Bone Mineral Density Over a 10-Year Period. (August 2014) - Fraser, Lisa-Ann; Adachi, Jonathan D.; Leslie, William D.; Goltzman, David; Josse, Robert; Prior, Jerilynn; Kaiser, Stephanie; Kreiger, Nancy; Kovacs, Christopher S.; Anastassiades, Tassos P.; Papaioannou, Alexandra; ,
Background: Many medications used in older adults have strong anticholinergic (ACH) properties, which may increase the risk of falls and fractures. Use of these medications was identified in a population-based Canadian cohort.Objective: To identify the fall and fracture risk associated with ACH medication use.Methods: Data collection and analysis were conducted at baseline, year 5, and year 10. Cross-sectional analyses were performed to examine associations between ACH medication use and falls. Time-dependent Cox regression was used to examine time to first nontraumatic fracture. Finally, change in bone mineral density (BMD) over 10 years was compared in ACH medication users versus nonusers.Results: Strongly ACH medications were used by 618 of 7753 participants (8.0%) at study baseline, 592 (9.5%) at year 5, and 334 (7.7%) at year 10. Unadjusted ACH medication use was associated with falls at baseline (odds ratio = 1.50; 95% CI = 1.14-1.98; P = 0.004), but the association was no longer significant after covariate adjustment. Similar results occurred at years 5 and 10. ACH medication use was associated with increased incident fracture risk before (hazard ratio = 1.22; CI = 1.13-1.32; P < 0.001) but not after covariate adjustment. Mean (SD) change in femoral neck BMD T -score over 10 years, in those using ACH medications at both years 0 and 5, was −0.60 (0.63) in ACH users versus −0.49 (0.45) in nonusers ( P = 0.041), but this was not significant after covariate adjustment.Conclusions: ACH medications were not found to be independently associated with an increased risk of falling, fractures, or BMD loss. Rather, factors associated with ACH medication use explained the apparent associations.